INCREASING THE INCOME OF MIE LIDI SME IN THE UNDERDEVELOPED VILLAGE OF BANJARSARI, DEMAK, INDONESIA, THROUGH THE UTILIZATION OF HYBRID INVERTER-BASED SOLAR ENERGY AND AUTOMATIC CONTROL - Pratomo, Sunu Arsy; Roehman, Fatchur; Purwanto, Purwanto; Setiawan, Muhammad Ikhsan (LPPM Univ. Ibn Khaldun Bogor, 2025)
The Community Service Program (PKM) aims to improve production efficiency and product quality of the Mie Lidi Small and Medium Enterprises (SME) in Banjarsari Village, Sayung District, Demak Regency, through the application of renewable energy-based technology. The technology implemented includes solar panels with a hybrid inverter and an automatic drying system with temperature control. This technology reduces dependence on PLN electricity, ensures consistent product quality despite adverse weather conditions, and lowers operational costs. As a result, production capacity increased by 25%, and the sustainability of the SME's operations was better ensured. Additionally, technical training and managerial assistance were provided to support efficient and sustainable business management.